The implication of Brexit on the financial market of the European Union and its regulation – legal and institutional aspects - Wicha, Agnieszka (Polish Review of International and European Law, 2023)
The Article tackled with the topic of the impact of Brexit on the EU financial market. The most important changes were identified and defined. Among different types of implications the Author chose those which were important for the shape of the EU financial market. The Article identified all crucial changes in the EU law regulating financial market. In the Article there was the analysis of the single passport rule in the context of Brexit and the sability of equivalency mechanism in this context. The changes in BMR and EMIR implied by Brexit were analysed.